Is there a vertical component to saccade targeting in Chinese reading?. (11th April 2013) - Zang, Chuanli; Meng, Hongxia; Liang, Feifei; Bai, Xuejun; Yan, Guoli
Abstract : In this study, we examined whether Chinese character structure influenced readers' saccadic targeting in Chinese reading. Readers' eye movements were recorded when they read single sentences containing one‐character or two‐character target words. Both the one‐character words and the two constituent characters of two‐character words either had a symmetrical left–right structure or a symmetrical top–bottom structure. Landing positions were very similar when readers initially fixated the target words with left–right and top–bottom structures. They targeted their initial saccades to the word centre in single fixation cases and to the word beginning in multiple fixation cases. Furthermore, there was a highly reliable effect that readers were more likely to target the lower half of a character than the upper half of the character regardless of its structure. The results suggest some vertical differentiation in initial saccadic targeting in Chinese reading, but that character structure does not modulate such targeting.